Humanist and Materialist Perspectives on Communication: The Work of Álvaro Vieira Pinto - Rafael Grohmann (tripleC: Communication, Capitalism & Critique)
The present paper recovers the notion of technology present in the works of the Brazilian philosopher Álvaro Vieira Pinto written during the 1970s. Pinto made humanist and materialist contributions to the study of communication(s). The paper connects the author’s contributions to communication theory with different theoretical and epistemological approaches, discussing the Zeitgeist of things, the post-human and the immaterial. Vieira Pinto anticipated theoretical questions that are relevant in current debates in communication theory.